An in‐vitro mechanical strain three‐dimensional culture model: periodontal ligament cell viability, apoptosis, and endoplasmic reticulum stress response. (5th March 2020) - Firth, Fiona A.; Milne, Trudy J.; Seo, Benedict; Farella, Mauro
Abstract : To develop a model to investigate a potential relationship between mechanical strain, cell responses, and endoplasmic reticulum stress in periodontal ligament (PDL) cells, primary PDL cell cultures were obtained from extracted premolars. Cells were cultured in hydrogel and subjected to 24 h of static mechanical strain, resulting in 18% dimensional substrate elongation. Cell viability, caspase‐3/7 activity, and mRNA levels for 28 genes, including unfolded protein response (UPR)‐related and mechanically responsive genes, serving as positive controls for stress induction, were examined. Compared with unstrained cultures, no difference in caspase activity was observed; however, viability responses differed between cell lines. Multiple UPR‐related genes were differentially upregulated, with marginal statistical significance, including cAMP responsive element binding protein 3 like 3 ( CREB3L3 ) (mean fold‐regulation = 1.91), an adenosine monophosphate‐dependent transcription factor with roles in UPR activation and the acute inflammatory response; and the pro‐apoptotic UPR gene, endoplasmic reticulum to nucleus signaling 2 ( ERN2 ) (mean fold‐regulation = 4.01). The observed effect on cell viability following strain with no change in caspase activity suggests that reduction in viability may be mediated via caspase‐3/7‐independent mechanisms. Three‐dimensional mechanical strain PDL cell culture models offer a method to study the role of endoplasmic reticulum stress and UPR, and provide a framework and potential UPR targets for future investigations.